Vortexes tune the chirality of graphene oxide and its non-covalent hosts - Di Mauro, A; Randazzo, R; Spanò, S F; Compagnini, G; Gaeta, M; D'Urso, L; Paolesse, R; Pomarico, G; Di Natale, C; Villari, V; Micali, N; Fragalà, M E; et al. (Chemical communications (Cambridge, England), 2016)
Graphene oxide (GO) is one of the most appealing bidimensional materials able to interact non-covalently with achiral molecules and to act as chiral inducers. Vortexes can tune chirality and, consequently transfer a specific handedness to non-covalent host molecules, either when dispersed in water or when deposited on a solid surface.